The Effect of Human Resource Management Practices on Motivation to Transfer: Evidence from the Malaysian Public Sector - Abdul Rahim Zumrah; Kalsom Ali; Ahmad Najaa' Mokhtar (UNIMAS Publisher, 2024)
Indexed by Scopus/MyCite